2022
DOI: 10.3390/cancers14205128
|View full text |Cite
|
Sign up to set email alerts
|

Improved Long-Term Survival of Patients with Recurrent Medulloblastoma Treated with a “MEMMAT-like” Metronomic Antiangiogenic Approach

Abstract: Medulloblastoma (MB) recurrence is usually incurable despite intensive therapy including high-dose chemotherapy. An evolving alternative approach to conventional chemotherapy aims at interfering with tumor angiogenesis at different levels. We report on a novel combinatorial metronomic antiangiogenic approach. The study is a retrospective observational study of 29 consecutive patients with first or multiple recurrences prospectively treated according to the MEMMAT strategy (“MEMMAT-like”) before the formal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 75 publications
(102 reference statements)
1
17
0
Order By: Relevance
“…Therefore, MEMMAT combined metronomic chemotherapy with the repurposing of nonchemotherapeutic drugs, as was previously done in the COMBAT (combined oral metronomic biodifferentiating antiangiogenic treatment) regimen . The rationale for combining the 5 oral drugs as well as bevacizumab and intraventricular therapy in MEMMAT has previously been described in detail …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MEMMAT combined metronomic chemotherapy with the repurposing of nonchemotherapeutic drugs, as was previously done in the COMBAT (combined oral metronomic biodifferentiating antiangiogenic treatment) regimen . The rationale for combining the 5 oral drugs as well as bevacizumab and intraventricular therapy in MEMMAT has previously been described in detail …”
Section: Discussionmentioning
confidence: 99%
“…This does not seem to be as good as the initial report of the MEMMAT regimen [ 26 ]. The Vienna team has also further reported that, out of 29 patients with medulloblastoma treatment with MEMMAT, 9 patients were alive, with a median of 44 months after recurrence [ 31 ]. Five out of nine surviving patients are currently in CR between 96 and 164 months after starting MEMMAT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The repartition of the molecular subtypes of brain tumors included might therefore influence the EFS in this series. Anyhow, in the series from Slavc et al [ 31 ] among the 23 patients whose tumors underwent molecular subgrouping classification using a DNA methylation array and brain classifier mnp-V12.5, group 4 medulloblastomas seem to group 4 have better outcome than group 3 medulloblastoma (median survival: 43 months (14–71) vs. not reached). As group 3 medulloblastomas are commonly accepted as displaying worse prognoses, the findings reported by Slavc et al [ 31 ] seem to further highlight the potential of MEMMAT for both relapsing Group 3 and 4 medulloblastomas, which represent medical unmet needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronomic, antiangiogenic strategies, such as the MEMMAT (metronomic and targeted antiangiogenesis therapy for children with recurrent/progressive medulloblastoma) protocol (NCT01356290), have thus been evaluated to offer a balance between therapeutic effectiveness and tolerability. 2 Such regimen comprises of oral and intraventricular chemotherapy, bevacizumab, and other repurposed agents, including thalidomide, fenofibrate, and celecoxib. Interim analysis from the MEMMAT study indicated a response rate of 45% and 5-year progression-free survival (PFS) of 24.6%, confirming the activity of this treatment approach.…”
Section: Gastric Outlet Obstruction In a Patient With Relapsed Medull...mentioning
confidence: 99%